2016
DOI: 10.3390/mi7060101
|View full text |Cite
|
Sign up to set email alerts
|

Affinity-Bead-Mediated Enrichment of CD8+ Lymphocytes from Peripheral Blood Progenitor Cell Products Using Acoustophoresis

Abstract: Acoustophoresis is a technique that applies ultrasonic standing wave forces in a microchannel to sort cells depending on their physical properties in relation to the surrounding media. Cell handling and separation for research and clinical applications aims to efficiently separate specific cell populations. Here, we investigated the sorting of CD8 lymphocytes from peripheral blood progenitor cell (PBPC) products by affinity-bead-mediated acoustophoresis. PBPC samples were obtained from healthy donors (n = 4) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Furthermore, acoustophoresis has been shown to be a gentle method which does not impact cell viability or functional capacity of the separated sample. 21,23,[27][28][29][30][31][32][33] There is a large size overlap between the different white blood cell populations with a median diameter (range) of 7.2 μm (5.5-10 μm) for lymphocytes, 9.5 μm (7.5-12 μm) for monocytes and 9.5 μm (8.5-11 μm) for granulocytes as determined by coulter counter measurements (Fig. S2 †).…”
Section: Concurrent Fractionation Of White Blood Cellsmentioning
confidence: 98%
“…Furthermore, acoustophoresis has been shown to be a gentle method which does not impact cell viability or functional capacity of the separated sample. 21,23,[27][28][29][30][31][32][33] There is a large size overlap between the different white blood cell populations with a median diameter (range) of 7.2 μm (5.5-10 μm) for lymphocytes, 9.5 μm (7.5-12 μm) for monocytes and 9.5 μm (8.5-11 μm) for granulocytes as determined by coulter counter measurements (Fig. S2 †).…”
Section: Concurrent Fractionation Of White Blood Cellsmentioning
confidence: 98%
“…Size based separation was successfully shown for a variety of clinical relevant applications such as separation of lymphocytes from granulocytes 36 , isolation of tumor cells 37 , separation of WBCs from platelets 38 , cell cycle phase synchronization in mammalian cells 39 and isolation of bacteria in blood from sepsis patients 10 . Furthermore, acoustophoresis has been shown to be a gentle method that does not affect the viability and proliferative capacity of acoustically-separated cells 38 , 40 43 .…”
Section: Introductionmentioning
confidence: 99%
“…They study levitation of zebrafish embryos using acoustic radiation force in a noncontact wall-less platform for a period of less than 2000 s, while the embryos still in development at 2-14 hours postfertilization, and they found that the levitation does not interfere the development, though it might influence mortality rate. Urbansky et al [40] perform the manipulation of peripheral blood progenitor cells (PBPCs) with the focus on sorting out CD8 lymphocytes (target cells) from the mixture that contains CD4, CD19, CD34, and CD56 lymphocytes as well. They label the CD8 with affinity beads, forming bead-cell complex, to modify the acoustic mobility of the target cells.…”
Section: Acoustophoretic Manipulation Of Bioparticlesmentioning
confidence: 99%